The Online Learning Creativity Using the Google Meet Platform in Vocational High Schools - Purwoko, Riawan Yudi; Primartadi, Aci; Efendi, Yosep; Amin, Thomas (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2022)
Online learning during the Covid-19 pandemic is still looking for the best model. One important capital is the availability of online learning platforms. However, no studies currently explain the learning process using a unique platform for creativity. This study aims to describe the perceptions of teachers and students in learning during synchronous learning using the Google Meet platform and their creativity. This research is a qualitative descriptive study. The subjects in this study were teachers and students in vocational high schools conducting online learning. Data collection techniques were carried out through observation, interviews, and surveys. The instruments used were observation sheets, interview guidelines, and questionnaires. Data analysis was done using the triangulation technique; then, the final result was analyzed using the percentage technique. Based on field research, it is known that the Google Meet application is more effective than other learning application media. The use of Google Meet that students and teachers are interested in certainly supports effective online learning during the Covid-19 pandemic because students are more controlled in synchronous learning and teachers are more creative because of the features that support the Google Meet platform. The stages of online learning, from planning, and implementation, to evaluation through the Google Meet platform, can be very well facilitated. Thus teachers can use Google Meet as an alternative platform to support online learning because it is relevant and integrated with other learning support features.